Analisis Pengaruh Covid-19 Terhadap Psikis Calon PNS dalam Mengikuti Ujian SKD Menggunakan Metode Certainty Factor - Nunsina (LPPM-UNIKI, 2021)
Currently the CPNS selection is a platform to take the civil servant candidate exam held by the government throughout Indonesia. During the COVID-19 pandemic, prospective civil servants are required to carry out an antigen swab test orPCR as one of the requirements for taking the SKD exam. With the many and strict regulations, prospective civil servantsexperience psychological problems with the exams they will face. There are 4 types of psychological disorders, namelypsychological responses to constraints and demands, physical responses, perceptual responses and physical responses.To reduce psychological disorders experienced by CPNS participants, this study uses an expert system using the certaintyfactor method. The goal is to find out the CPNS psychological condition and what solutions should be given. Therefore,to make it easier to make decisions for CPNS in taking the SKD exam, a web decision-making system is needed that willperform psychological classification of prospective examinees to obtain results from the doubts experienced by theseparticipants. The purpose of this research is to design and build an application to determine the psyche of prospectiveparticipants in determining doubts about the requirements required by the government. The method used in this study isthe Certainty Factor method. This method is a decision-making method in solving problems that occur from anopportunity or event that depends on the outcome of the incident. The data collection method was carried out in threestages, namely literature studies, field studies, and system design and implementation studies. The targeted output of thisresearch is a web decision-making system